Indentation testing on 3 MeV proton irradiated tungsten. (December 2020) - Rayaprolu, R.; Möller, S.; Abernethy, R.; Rasinski, M.; Haley, J.C.; Linsmeier, Ch.
Highlights: High dose rate proton irradiation (1 × 10 −04 –5 × 10 −5 ). Blisters in tungsten observed and subdued using higher currents. Macro-indentation results compared with nano-indentation results. Transmission electron microscopy conducted post irradiation. Abstract: Tungsten samples have been irradiated with 3 MeV protons with dose rates of 1 × 10 - 04 to 5 × 10 - 05 dpa/s to doses of 0.01–0.67 dpa at 360 K in a pilot experiment. Micro- and macro-indentation were used to measure irradiation hardening in the samples. An initial irradiation hardening of 1.23 ± 0.09 GPa and 1.88 ± 0.83 GPa was measured by micro and macro indentation. The irradiation hardening was observed to saturate at 0.03 dpa damage. Dislocation loops were identified using TEM suggesting an increasing loop size with dose.